DEVELOPMENT OF SAFE METHODS FOR SERVICING TRANSFORMERS AT LOW AND MEDIUM HEIGHTS - Tolibov Muhammad Erkin o’g’li; Ibragimov Anvar Rustam o’g’li; Kаримов Ташмухамед Халмухамедович; Арипов Нуритдин Юсупович (Web of Journals Publishing, 2024)
IN this article, we will discuss the possibilities of using a suspended hydraulic unit to safely service oil-immersed transformers at high and low altitudes.
Keywords: transformer, electrical insulation , cooling, maintenance, regular monitoring, automation and alarms.